Did Moses Permit Divorce? Modal wěqāִtal as Key to New Testament Readings of Deuteronomy 24:1-4 - Warren, Andrew (Tyndale bulletin, 1998)
The New Testament discussions of divorce, both in Matthew 19 and elsewhere, are dominated by a distinction between Permission and Obligation. It is generally assumed that the debate arises from a ‘presupposition’ of divorce in Deuteronomy 24. An improved syntactic analysis of the Old Testament text shows Moses to have in fact issued a specific directive on divorce, but in such a way that it was open to the kind of misunderstanding that we see corrected by Jesus. This analysis is supported by all the New Testament texts. By applying the categories of linguistic modality to main-clause verbs, verbs of reporting, verbs of divorcing and conditional clauses, it is possible to shed more light on how Jesus and the Pharisees dealt with the Old Testament text, and to show just what was wrong with the Pharisees’ understanding of Hebrew grammar.